2019
DOI: 10.1177/1550059419868872
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Band Auditory Steady-State Response as a Neurophysiological Marker for Excitation and Inhibition Balance: A Review for Understanding Schizophrenia and Other Neuropsychiatric Disorders

Abstract: Altered gamma oscillations have attracted considerable attention as an index of the excitation/inhibition (E/I) imbalance in schizophrenia and other neuropsychiatric disorders. The auditory steady-state response (ASSR) has been the most robust probe of abnormal gamma oscillatory dynamics in schizophrenia. Here, we review recent ASSR studies in patients with schizophrenia and other neuropsychiatric disorders. Preclinical ASSR research, which has contributed to the elucidation of the underlying pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 116 publications
1
49
0
Order By: Relevance
“…Although speculative, locations of smaller local networks may spatially vary in individuals compared to those of macro networks via large structures. Lastly, findings of resting-state gamma abnormalities may not generalize to more commonly studied stimulus-driven forms of gamma-band responses (54,(57)(58)(59). Future studies are needed to assess the relationships among spontaneous gamma activity at rest with gamma oscillations that are generated in response to 40-Hz stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although speculative, locations of smaller local networks may spatially vary in individuals compared to those of macro networks via large structures. Lastly, findings of resting-state gamma abnormalities may not generalize to more commonly studied stimulus-driven forms of gamma-band responses (54,(57)(58)(59). Future studies are needed to assess the relationships among spontaneous gamma activity at rest with gamma oscillations that are generated in response to 40-Hz stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalographic and magnetoencephalographic recordings can be used to noninvasively detect ASSRs in humans, which show a peak frequency at 40 Hz ( Pastor et al, 2002 ). A number of studies on the 40-Hz ASSR have reported reductions in the evoked power and phase-locking measures (i.e., inter-trial phase coherence) in individuals with schizophrenia (SZ) ( Thune et al, 2016 ; Tada et al, 2019 ). The reduction of 40-Hz ASSR has been proposed as a biomarker of the N-methyl-D-aspartate receptor (NMDAR) hypofunction in SZ patients ( Sivarao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, long ISI (20 s) used in this study might decay the noise level at the mid-time point of ISI. An increase in induced gamma power has been reported in schizophrenia in relatively short ISIs (~1-3 s) during auditory steadystate stimulation [37][38][39]. Regardless, it suggests that the evokedgamma power deficit is not simply caused by elevation of spontaneous power during the click-train stimulus period.…”
Section: Discussionmentioning
confidence: 91%
“…Time 0 is tone onset. The red dashed area(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) Hz frequency and during 200 ms before cessation of the click train) was for the following ASSR analyses. b Evoked-power amplitudes at 35-44 Hz during 200 ms before cessation of click-train stimuli were obtained by time-frequency decomposition of averaged LFP trace across 50 trains of stimuli following subtraction of spontaneous power amplitude (z-score, 200-ms segment) at the midtime point of the ISIs (20-s duration) from LFP power amplitude (z-score…”
mentioning
confidence: 99%